ARCA e Fundação o Boticário [manuscrito]: uma perspectiva sobre o movimento ambientalista contemporâneo (1980-2000) - BORGES, Rafael Gonçalves (2009)
The work proposed herewith, entitled ARCA and Fundação O Boticário: a perspective about the environmental movement contemporary , is an analysis which aims to examine the consolidation of environmental discourse over the last two decades of the twentieth century through a study of the environmental movement in its main characteristics, putting in discussion the insertion of it in the context of substantial changes occurred in the period, concerning to civil associations in network and the scientific-technical development, which form the basis for the emergence of an ethical imperative of responsibility and of a defense of a biological and environmental identity.